(untitled) (Journal of Mathematical Modeling and Fractional Calculus, 2024)
This work analyzes the COVID-19 fractional order SEIQRD compartmental model using the six primary categories of the Caputo approach. Numerous conclusions have been drawn on the the solution’s boundedness and non-negativity, as well as the existence and uniqueness of the new mod el. Our findings reveal that the When R0 < 1, the system is locally asymptotically stable at infection-free equilibrium. We also observed that In the absence of illness, the system is globally asymptotically stable (R of Covid 19 <1). This study’s primary goal is to look into the dynamics of COVID-19 transmission in Italy, the nation where the virus was initially discovered in January 2020. To account for the uncertainty arising from the limited knowledge about the Corona virus (COVID-19), The order of fractions A fractional order was used to apply the SEIQRD compartmental model framework. The dynamics of the equilibrium are examined using the La Salle invariant principle and the Routh-Hurwitz consistency criterion. Additionally, the suggested model’s approximate solution is calculated using the fractional-order Taylor’s method. Through the comparison of simulation results with empirical data, the model’s validity is shown. The study’s findings regarding the impacts of using face masks showed that wearing face masks frequently can prevent the COVID-19 virus from spreading.